ANALISIS FAKTOR PENYEBAB REPEAT EXPOSURE CITRA DIGITAL DENGAN MENGGUNAKAN COMPUTED RADIOGRAPHY (CR) - Dwi Lestari; Fatimah (Perhimpunan Radiografer Indonesia (PARI), 2019)
Background:Repeat Analysis Program is a documenting system of digital image repetition and determining cause of them, so it can be minimize or reduce repetition number. The research purposes are to know percentage of exposure repetition, causative factor of repetition and to determine the solutions for reduce repetition number. Methods: This type of this research is a descriptive quantitative with a survey method approach. Data was taken since March to April, 2018 at Radiology Installation of Islamic Hospital Klaten by took some samples of digital image exposure repetition from all radiological examinations either contrast or not. Being did Focus Group Discussion with five respondents. Data was processed and made a Pareto diagram to knew the cause of dominant factor for digital image repetition and made a fishbone diagram to determined the solution based on the cause of image repetition. Results: Results showed a total repeat rate at March to April 2018 is 3,43%. The result is surpass the remommended limit of KMK No. 129/Menkes/SK/II/2008 which ≤ 2%. The main cause is positioning (43,06%), and the type of examination that is thorax (57,66%). Conclution: The solutions are to improve the radiographer skills in positioning non-cooperative patients, determination of exposure factor, and giving education to patient.